Accidental ingestion of swamp stone: A new and hazardous source of lead poisoning - Abbas Aghabikloo (Wiley, 2021)
Abstract It is important to find sources for lead poisoning and educate the population about the danger of this heavy metal. The epidemiologic studies for evaluating BLL can help develop a guideline for screening endangered populations and providing treatment.